2018
DOI: 10.1002/ncp.10110
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Standardized Phase Angle, Nutrition Status, and Clinical Outcomes in Surgical Cancer Patients

Abstract: SPA was associated with different nutrition status parameters, and it was able to predict postoperative infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 39 publications
0
52
0
5
Order By: Relevance
“…A study of adult mixed solid tumor patients scheduled to undergo surgical treatment found a mean of −0.87 ± 1.43, and 28.1% of their population was SPhA <−1.65. 37 Similarly, in a study of mixed solid tumor patients about to undergo radiation therapy 27% of patients presented with SPhA <−1.65. 38 Finally, in the study of HSCT patients Note: All response for event YES.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study of adult mixed solid tumor patients scheduled to undergo surgical treatment found a mean of −0.87 ± 1.43, and 28.1% of their population was SPhA <−1.65. 37 Similarly, in a study of mixed solid tumor patients about to undergo radiation therapy 27% of patients presented with SPhA <−1.65. 38 Finally, in the study of HSCT patients Note: All response for event YES.…”
Section: Discussionmentioning
confidence: 98%
“…The values of SPhA at diagnosis in our study are higher than those found in previous literature utilizing SPhA in an oncology setting. A study of adult mixed solid tumor patients scheduled to undergo surgical treatment found a mean of −0.87 ± 1.43, and 28.1% of their population was SPhA <−1.65 . Similarly, in a study of mixed solid tumor patients about to undergo radiation therapy 27% of patients presented with SPhA <−1.65 .…”
Section: Discussionmentioning
confidence: 99%
“…PA has been studied by a number of authors as a biological marker to evaluate prognoses of clinical pathologies, such as a cross-sectional and prospective study that evaluated the correlation between phase angle values and nutritional and clinical variables in cirrhotic patients with a sarcopenic profile (1) . In this study, it was concluded that low PA values can be good predictors for the diagnosis of cirrhosis and suggest its use as a viable marker for sarcopenia in patients with this profile because, in addition to being an easy-access method, it offers good reproducibility and low cost (21) .…”
Section: Discussionmentioning
confidence: 99%
“…biomarker stands out, used to estimate intra and extracellular fluid, predicting with this information the cellular health, size and integrity. The measurement values of this biomarker are expressed in degrees, which commonly range from 0º to 10º, and some studies mention values up to 15º (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Achado diferentes foram descritos por Axelsson et al, 12 14,15 Dindo et al, 15,16 (intervenções farmacológicas, transfusão) e 15,0% grau III, IV (internação prolongada,…”
Section: Discussionunclassified